OWNER-MANAGER AS CENTRAL FIGURE IN IMPLEMENTATION OF PRODUCTION MODELS FOR INDUSTRIAL MEXICAN SMEs. - Espinoza Méndez, Fernando; Espinoza Méndez, Eligio (Atenas, 2015)
At present we are living the phenomenon of globalized competitiveness, where the enterprises no matter their size, constantly are developing strategies to survive. This article is based on a literature research about the impact of performance of the national and international industrial Small and Medium Enterprises (SMES) in the worldwide economy and the problems that Mexican SMEs face in the implementation of production models, from the perspective of the role that plays the owner-manager. Factors are highlighted as: way of running a business, leadership, personal culture, and administrative, technological and social preparation. It concludes, with a comparative analysis of SMEs study case in three states of Mexico.